Pengaruh Latihan Beban Resistance Band Terhadap Kecepatan Shooting pada Permainan Sepakbola Siswa MA Darussalam Patalassang Kabupaten Sinjai - Zulfahmi; Afni, Nur; Akib, Puang Lamakkasau; Banawati, Anita Tri; Buswan, Muh. Bahrur Rahman; Arfanda, Poppy Elisano; Juhanis (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to determine the effect of resistance band weight training on shooting speed in soccer games for students of MA Darussalam Patalassang, Sinjai Regency. This study uses a quantitative approach with an experimental method and a One Group Pretest-Posttest Design. The population in this study were all students of MA Darussalam Patalassang, with a sample of 35 students selected according to research needs. Data collection was carried out through a shooting skills test measured using a stopwatch to see the speed before and after treatment. Data analysis techniques used include descriptive analysis, normality test, and hypothesis testing using the t-test. The results showed that there was a significant effect of resistance band weight training on increasing shooting speed in soccer games for students of MA Darussalam Patalassang, Sinjai Regency. Thus, resistance band training can be used as one of the training methods to improve students' shooting abilities in soccer games